(untitled) (Revista Direito em Debate, 2023)
The current society, marked by the technological revolution, has enabled the creation of new virtual communication spheres, notably with the emergence of the internet. Hate opinions disseminated through these new environments have gained notoriety in academic debates, as digital spaces, especially with social media, have reshaped the dynamics of spreading such opinions. Guided by the dialectical logic of "us against them," segregating discourses often target vulnerable minorities, as the fear of "the other" acts as a legitimizing factor for intolerance. This article aims to demonstrate the overcoming of hate speech through the foundations of Fraternal Law Metatheory. The research problem is to identify ways to eliminate hate speech, and the general objective is to demonstrate the possibilities of fraternity in confronting hate speech. The methodological construction used is based on the assumptions of Fraternal Law Metatheory, which presupposes a critical-constructive analysis of social phenomena through the unveiling of paradoxes. It is hoped that this study will contribute to expanding the perspective of equity and reducing hatred through the legal field.